Study of first sexual maturity in female bluefin tuna (Thunnus thynnus) from the central Mediterranean Sea - Susca V.; Bridges C.R. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
This preliminary study indicates that the minimum size at maturity is 110 cm (LF) in female bluefin tuna (BFT) from the Mediterranean Sea. It is notable that pre-adult specimens (with LF ranging from 100 to 110 cm) showed signs of gonadal development, characterized by the appearance of oocytes in the lipid stage. This finding occurred contemporaneously to both the appearance of E2 and Vtg in the plasma. The evidence of the present study needs to be confirmed in a larger fish sample including sampling at the different phases of the reproductive cycle.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)